2009
DOI: 10.1002/bit.22366
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a gastrointestinal tract microscale cell culture analog used to predict drug toxicity

Abstract: The lining of the gastrointestinal (GI) tract is the largest surface exposed to the external environment in the human body. One of the main functions of the small intestine is absorption, and intestinal absorption is a route used by essential nutrients, chemicals, and pharmaceuticals to enter the systemic circulation. Understanding the effects of digestion on a drug or chemical, how compounds interact with and are absorbed through the small intestinal epithelium, and how these compounds affect the rest of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
189
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 41 publications
(39 reference statements)
5
189
0
Order By: Relevance
“…In particular, we mention here the Ingber group at Harvard University, [14][15][16] who did pioneering work on ''organ-on-a-chip'' devices and the Shuler group at Cornell University who have pioneered the development of in vitro analogues to physiologically-based pharmacokinetic (PBPK) models. [17][18][19][20][21] Such micro-scale devices have the potential to accurately produce physiologically realistic parameters and can closely model the desired in vivo system to be tested. In a recent publication, Kim et al 16 reported a ''human gut-on-a-chip'' microdevice, which was composed of a confluent layer of intestinal epithelial (Caco-2) cells cultured on a porous membrane.…”
Section: Fitting the Biological Model Into A Microfluidic Setupmentioning
confidence: 99%
“…In particular, we mention here the Ingber group at Harvard University, [14][15][16] who did pioneering work on ''organ-on-a-chip'' devices and the Shuler group at Cornell University who have pioneered the development of in vitro analogues to physiologically-based pharmacokinetic (PBPK) models. [17][18][19][20][21] Such micro-scale devices have the potential to accurately produce physiologically realistic parameters and can closely model the desired in vivo system to be tested. In a recent publication, Kim et al 16 reported a ''human gut-on-a-chip'' microdevice, which was composed of a confluent layer of intestinal epithelial (Caco-2) cells cultured on a porous membrane.…”
Section: Fitting the Biological Model Into A Microfluidic Setupmentioning
confidence: 99%
“…The intestines, a barrier that must be passed by all swallowed drugs, seem surprisingly easy to model (see 'Just cells'): using cell lines representing only the gut epithelium, mucin-secreting cells and lymphocytes, Shuler and his colleagues have been able to recreate the mucoid layer in the gut 5 . With the help of an absorbent polymer gel that can be used to build microscale scaffolding, the team has even crafted a collagen structure to represent the villi that line the intestinal wall 6 .…”
Section: From Animals To Organsmentioning
confidence: 99%
“…Our most realistic tissue construct is the GI tract which contains cell lines that mimic three cell types in appropriate ratios. [12][13][14] A major component of the current call for proposals from DARPA, NIH, and DTRA is for more biologically authentic tissues. Colleagues with in-depth expertise in tissue engineering have much to contribute in this regard.…”
Section: Living Cell Models Of Humansmentioning
confidence: 99%
“…14 The GI tract model has been coupled with systemic circulation to observe interaction of the GI tract with a liver compartment in terms of acetaminophen toxicity. 13 The presence of the GI tract modulated the amount of acetaminophen delivered to the liver. Predictions of response to high concentration of acetaminophen were similar to that observed in rodent studies.…”
Section: Living Cell Models Of Humansmentioning
confidence: 99%